Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia - Prieto, Carlos; Lorenc-Brudecka, Jadwiga (Zootaxa, 2017)
A preliminary assessment of barcode data for the genus Rhamma suggests the presence of several cryptic species in Colombia. Based on morphology and barcodes, we were able to diagnose one of these lineages as a new species that is described herein as Rhamma dawkinsi, sp. nov. Adult specimens and the genitalia of both sexes are illustrated and compared with R. adunca (Draudt, 1919) and R. comstocki (Johnson, 1992), the most closely related species based on phenotypic appearance.